It's a magical world : a Calvin and Hobbes collection - Watterson, Bill. (Kansas City, Mo. : Andrews and McMeel, 1996)
Collects approximately 280 "Calvin and Hobbes" comic strips, which chronicle the adventures of a rambunctious little boy and his tiger companion.
5.5
5-8
5-8
GN 480
Keywords: Calvin (Fictitious character : Watterson) -- Fiction; Cartoons and comics; Calvin (Fictional character : Watterson) -- Fiction; Comic books, strips, etc